Metacognitive and cognitive reading strategies used by ESL learners while reading in print and hypertext / Cynthia Yolanda Doss - Cynthia, Yolanda Doss (2009)
This study investigates the differences in the choice of metacognitive and cognitive strategies employed by second language learners while reading expository texts in print and hypertext. The research sample comprised 10 students from the Faculty of Law, Universiti Teknologi MARA, Shah Alam. The subjects were required to verbalise their thoughts while reading in print and hypertext. They were asked to read and say everything either in their L1 or English aloud regardless of how trivial the thinking seemed. A number of instruments were used in this study. A questionnaire (Student’s Profile) was given at the beginning to obtain information on the subjects. The questions ranged from age to age, level and type of education to proficiency in the English Language. Another questionnaire The Online Survey of Reading Strategies (OSORS) was given after the subjects had written the summary for the hypertext. The 38 items of the OSORS were about their perception of the on-line reading strategies that they used. Both expository texts, the printed and hypertext used in the study had a predetermined 12th grade readability level. The hypertext was designed to have six hyperlinks which the students could access. A retrospective interview was used to supplement the think aloud procedure. This was done so as to probe into some of the statements made during the think aloud, thereby improving the reliability of the protocol analysis. iv A coding scheme of reading strategies was adapted from Sheorey and Mokhtari (2001), and Anderson (1991, 2003) assisted in identifying and determining which reading strategies students employed when reading the printed and hypertext. The data from the verbal reports, questionnaire and summary were analysed in a variety of ways. These include using frequency counts, percentage scores, mean scores, T-test, Spearman correlation analysis and the Wilcoxon test of significance. The findings in general revealed that there was no real significant difference in the choice of strategies used when reading printed and hypertext except for these reading strategies; determine what to read, prior knowledge, use text features and try to stay focused. The ESL learners used more of these strategies when reading hypertext than printed text. Also most of the scores the students obtained for the summary of the printed text were better than the hypertext. The findings of the study hold important implications for the reading curricula, teacher and research concerned with improving the ESL learners reading skill in hypertext.